Pengaruh Bokasi Kulit Pisang dan Pupuk NPK Grower terhadap Pertumbuhan serta Produksi Tanaman Tomat (Solanum lycopersicum) pada Tanah PMK - Nurhidayati, Siti; Maizar, Maizar; Maharani, Tati (UIR PRESS, 2026)
This study aims to determine the effect of banana peel bokashi and NPK Grower fertilizer on the growth and production of tomato (Solanum lycopersicum) on red-yellow podzolic soil. The study entitled Effects of banana peel fertilization and NPK Grower fertilizer on the growth and production of tomato plants (solanum lycopersicum) on FMD soil was carried out at the Experimental Field of Islamic University of Riau, started from June to September 2022. The study used a Completely Randomized Factorial Design consisting of 2 factors. The first factor was Banana Peel Bokashi (P) with 4 treatment levels (0, 125, 250, and 375 g/polybag). The second factor was NPK Grower Fertilizer (N) with 4 treatment levels (0, 5, 10 and 15 g/polybag). Parameters observed were plant height, number of productive branches, flowering age, harvest age, number of fruits per plant, fruit weight per plant, fruit weight per fruit, and number of remaining fruits. The data were analyzed with ANOVA and continued with the honest significant difference test (HSD) at the 5% level. The results showed that interactively the effect of banana peel bokashi and NPK Grower fertilizer had a significant effect on plant height, number of productive branches, flowering age, harvest age, number of fruits per plant, fruit weight per plant, fruit weight per fruit, and the number of remaining fruits. The best treatment was found in 375 g/polybag of banana peel bokashi and 15 g/plant of NPK grower fertilizer.